Phosphorylation of Sp1 by Cyclin-dependent Kinase 2 Modulates the Role of Sp1 in CTP: Phosphocholine Cytidylyltransferase α Regulation during the S Phase of the Cell Cycle - Banchio, Claudia Elena (2004)
Phosphatidylcholine is the major lipid component in mammalian membranes. Phosphatidylcholine synthesis increases in C3H10T1/2 fibroblasts during the G1 and S phases of the cell cycle. Previous studies demonstrated that the mRNA encoding CTP:phosphocholine cytidylyltransferase (CT ) increases during S phase (Golfman, L. S., Bakovic, M., and Vance, D. E. (2001) J. Biol. Chem. 276, 43688–43692) and that this activation is driven by increased binding of Sp1 to the CT promoter (Banchio, C., Schang, L. M., and Vance, D. E. (2003) J. Biol. Chem. 278, 32457–32464). We now demonstrate that cyclin-dependent kinase 2 (CDK2) phosphorylation of Sp1 activates CT transcription during S phase. Sp1 binds in a phosphorylated state to the CT promoter. Sp1 binding is enhanced by association with cyclin A/E and CDK2, both in vivo and in vitro. In cells that overexpress Sp1, co-expression of cyclin A and CDK2 induces a high and constant level of CT expression, whereas reduction in the expression of cyclin A, cyclin E, and CDK2 eliminates the induction of CT expression in S phase. Furthermore, CT expression is decreased in cells overexpressing a dominant-negative form of CDK2 and in cells treated with the CDK2 kinase inhibitors roscovitine and olomoucine. These results enhance our understanding of the regulatory mechanisms involved in the expression of CT in preparation for cell division.